A History of “Who Speaks for Islam?” in Bosnia-Herzegovina: An Official Versus Popular Islam Debate - Hüsrev Tabak (Gazi Akademik Bakış)
This paper examines the organisation of popular and official Islam during and after communism in Bosnia-Herzegovina. Through studying the interaction between the popular and the official forms of Islam in the historical context, this paper unfolds the debate on who speaks for Islam? That took place between official representatives and popular Islamic groups and movements in the former Yugoslavian republic. Such an enquiry revealed firstly that a close contact with the existing regime (regardless of its ideology) is essential for becoming and remaining as the official Islamic authority, as seen in the Islamic Community’s pro-Titoist stance throughout in the former Yugoslavia. The findings of the enquiry secondly suggest that popular Islam and official Islam represent transitive positions; meaning that a popular Islamic movement can become the official Islam, vice versa. Accordingly, a former popular Islam front, the Mladi Muslimani (Young Muslims), in Yugoslavia evolved into an official Islamic authority after the dissolution of the country and by the Bosnia-Herzegovina’s establishment, in the scope of which new popular Islamic groups bred.